PENYULUHAN KESEHATAN MENGENAI HIPERTENSI PADA IBU HAMIL DI POLIKLINIK RUMAH SAKIT AN-NISA 2023 - Titin Anisah; Indri Yana Sari; Sulistikawati; Lala Nur Sahila; Putri Izza Alzamy; Lilis Ulandari; Titi Widiyanti; Melly Sa’idah; Ajat Sudarjat; Meily Purnamasari; Luxiana Rahayu; Nuryani; Febi Ratnasari (Yayasan Nusantara Hasana Berdikari, 2023)
Hypertension in pregnancy is a non-communicable disease that causes maternal death. Non-communicable diseases (PTM) are chronic diseases that are not transmitted from person to person. PTM include hypertension, diabetes, heart disease, stroke, cancer, and chronic obstructive pulmonary disease (COPD). PTM is the cause of death for nearly 70% in the world. According to the results of Basic Health Research (Riskesdas) in 2007 and 2013, there appears to be a tendency for the prevalence of PTM to increase, such as hypertension, diabetes, stroke, and joint/rheumatic/gout diseases. This phenomenon is predicted to continue (Ministry of Health RI, 2018). Research objectives to knowing the relationship between knowledge, attitudes, and eating patterns with the incidence of hypertension in pregnant women at AN-NISA Hospital. Short training by providing material on good dietary standards for hypertensive patients in pregnant women. Then re-screening will find out the level of decrease in high blood pressure scale of hypertensive patients in pregnant women after changing regular eating patterns, so as to get maximum results for hypertensive patients in pregnant women.